STRUCTURAL AND ECOPHYSIOLOGICAL PLASTICITY OF SOME EVERGREEN SPECIES OF THE MEDITERRANEAN MAQUIS IN RESPONSE TO CLIMATE (PHOTOSYNTHETICA, 1995)
The most representative evergreen shrub species growing in the low mediterranean maquis modified their leaf characteristics during the year, but the response to climate varied among the species. The real sclerophyllous species, Quercus ilex L., Phillyrea latifolia and Pistacia lentiscus, showed a convergence in higher leaf thickness and lower, net photosynthetic rate (PN) compared with Arbutus unedo L. and Cistus incanus L. Under summer stress they maintained a substantial positive carbon balance. Pistacia was one of the most tolerant species to the drought, it maintained a substantial positive balance over a wide range in temperature. Arbutus and Cistus had relatively thin leaves with a higher succulence index and higher PN over the more characteristic sclerophyllous species. The superiority of Cistus in carbon uptake over all the spacies was maintained throughout most of the year by its morphological leaf properties. low leaf thickness, high chlorophyll contents. Besides, Cistus shed most of its leaves before summer, thus reducing its evaporative surface.